Rancang Bangun Sistem Informasi Manajemen Aset “SIMA+” Berbasis User Centred Design (UCD) - Murdiaty Murdiaty; Angela Angela; Cindy Aprilia; Nuraina Nuraina (STMIK Budi Darma, 2021)
Assets consist of immovable and movable objects, both tangible and intangible assets, which are included in the fortune of an agency, organization, business entity or individual. The wrong management of assets will be bad for the company so that it is resulting in losses. Utilization of assets cannot be carried out optimally because they are not clearly identified, making it difficult to know which assets can still be used or when it is time to replace them and when it is time to carry out maintenance. Assets really need to be managed and utilized properly in order to maintain high asset value and to achieve optimal use and utilization of assets so as to provide more benefits for the company. The purpose of this research is to develop an asset management information system called SIMA+. The system development methodology used is prototyping. The system design uses Microsoft Visual Studio 2015 with the programming language Visual Basic, the system output design uses Crystal Report, and data storage uses Microsoft SQL Server 2014. The result of this paper is a system that is expected to have the ability to maintain asset value, asset service life, and asset security, minimizing asset utilization transaction errors and can adjust asset data recorded in the system and physical asset data.